The Impact of Two Different Transfusion Strategies on Patient Immune Response during Major Abdominal Surgery: A Preliminary Report - Kassiani Theodoraki; Maria Markatou; Demetrios Rizos; Argyro Fassoulaki (Journal of Immunology Research)
Blood transfusion is associated with well-known risks. We investigated the difference between a restrictive versus a liberal transfusion strategy on the immune response, as expressed by the production of inflammatory mediators, in patients subjected to major abdominal surgery procedures. Fifty-eight patients undergoing major abdominal surgery were randomized preoperatively to either a restrictive transfusion protocol or a liberal transfusion protocol (with transfusion if hemoglobin dropped below 7.7 g dL−1 or 9.9 g dL−1, respectively). In a subgroup of 20 patients randomly selected from the original allocation groups, blood was sampled for measurement of IL-6, IL-10, and TNFα. Postoperative levels of IL-10 were higher in the liberal transfusion group on the first postoperative day (49.82±29.07 vs. 15.83±13.22 pg mL−1, P<0.05). Peak postoperative IL-10 levels correlated with the units of blood transfused as well as the mean duration of storage and the storage time of the oldest unit transfused (r2=0.38, P=0.032, r2=0.52, P=0.007, and r2=0.68, P<0.001, respectively). IL-10 levels were elevated in patients with a more liberal red blood cell transfusion strategy. The strength of the association between anti-inflammatory IL-10 and transfusion variables indicates that IL-10 may be an important factor in transfusion-associated immunomodulation. This trial is registered under ClinicalTrials.gov Identifier: NCT02020525.